Phenotypic characterization of local Peranakan Etawa goat reared in Polman regency, West Sulawesi. Issue 1 (April 2020) - Rahim, L; Bugiwati, S R A; Dagong, M I A
Abstract: Goats are one of the mainstay commodities for farmers in rural areas, especially in several development centers in the West Sulawesi region, Indonesia. Generally the local goats that are kept are Kacang goats which are the type of meat production, but since the introduction of the Etawa breed most of the goat population that is currently being kept is from the Peranakan Etawa (PE) goat which is a cross between Kacang and Etawa goats which later develop into dual-purpose goats (meat and milk). The purpose of this study was to characterize the phenotypic (qualitative and quantitative) properties of Peranakan Etawa (PE) goats which were maintained by communities in the West Sulawesi region, Indonesia. This study used a survey method by identifying the qualitative and quantitative performance of the PE goat population. Characterization activities carried out were to identify the performance criteria of qualitative traits which included the characteristics of coat color, horn and ear shape and quantitative properties such as body weight, height, body length and chest circumference and chest width. A total of 113 goats (111 females and 2 male Peranakan Etawa breeds) were selected to be used as samples from the existing goat population. Peranakan Etawa breeding performance based on morphometric data included the characteristics of shoulder height (67.98 ± 5.61 cm), back height (71.34 ± 5.73 cm), body length (71.70 ± 6.46 cm), chest circumference (72.19 ± 6.46 cm), chest width (15.41 ± 1.86 cm) and body weight (33.04 ± 6.09 kg). The qualitative and quantitative performance of Etawa breeds in West Sulawesi is very diverse and need genetic improvement to meet Indonesia National Quality Standards (SNI).